St. Claire's Chruch - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the interior of St. Claire's Church. The front altar is decorated with candles, and the the center of the altar has a dome topped with a Catholic cross. A stained glass window depicting the Last Supper is visible above the altar. On the left of the altar, a man is standing on a ladder.